A constituição da docência no ensino superior em Letras: de professor da educação básica a docente universitário - Lenz, Noemi (2010)
This investigation is inserted in the research line Education, Knowledge and Professional Development, from the Postgraduate Program in Education, Master Degree in Education at the Federal University of Santa Maria, RS. Through this research we sought to understand the paths / the routes experienced / lived by four active professors in the Language Course, from their initial development, going through their teaching path in elementary schools, getting to their current journey as college professors. In addition, we attempted to investigate how elementary school teaching experience reflects in their professional acting as future teachers professors (educators / instructors), in the course of their professional path, interfering in their development. The methodology is qualitative for it aimed at learning the phenomenon in its essence, at the same time that the sociocultural narrative approach was used through semi-structured narrative interviews, to understand the participating teachers voices/speeches/narratives. It has as methodological theorethical basis authors such as Taylor and Bogdan (1987), Chizzotti (2008), Bolzan (2001, 2002), Cunha (1997, 2008), Bakhtin (1999, 2003) and Liev S. Vygotski (1988, 1995, 2000, 2008), which grounds the qualitative research, at the same time it represents the sociocultural narrative point of view, because it permits to comprehend the processes lived/experienced by the subject and which are capable of changing him/her when clarifying his/her conceptions and ideas regarding his/her practices. Thus, this procedure is justified, for the subject, when narrating, when giving voice to his/her own conceptions, [re] signifies them, therefore becoming a space which allows him/her to reflect about his/her pedagogical acting, constituting above all a formative place. Semi-structured interviews were done with the collaborator-subjects, being them college professors who teach at the Language Course. Moreover, the theoretical weaving of this research finds bases in the learning theorists sociocultural studies - Liev S. Vygotski (1988, 1995, 2000, 2008), Luria (1988) and Leontiev (1988, 2006), Bakhtin (1992, 1999), as well as authors who discuss teachers education, such as Anastasiou (2002, 2004), Cunha (1997, 2008), Bolzan (2001, 2002, 2006, 2007, 2008), Isaia and Bolzan (2007, 2008), Isaia (2005, 2006), García (1989, 1997), Nóvoa (1997), Huberman (1992), Schön (1997, 2000), Zeichner (1997), Pimenta (2002), Tardif (2003) and Kincheloe (1997). After mapping these findings, the following analysis categories emerged: to learn teaching, education processes and pedagogical activity. The analysis of the findings allows us to affirm that teaching is a continuous and permanent construction, based on a studying teaching activity and that, for this, the engendered movements influence in the union of the personal pathway elements towards the professional path. This is possible when the idea of teachers education programs are considered, and which go beyond the prescriptive and standardized nature, as if everyone learned thorough the same formative movements. The participants teaching work is grounded on research, demarcating that this is the process which allows them to reflect about their practice. This process brings forth the awareness of the necessity of keeping in a constant construction process, continuously learning to be teachers, in the course of the pedagogical activity development, something which permits to produce the shared reflexive processes. This nature of producing teaching is that makes it possible to understand it as a professional activity, demarcating the teaching professio nalism. Furthermore, it was possible to comprehend that the participants teaching conceptions refer to an understanding of education in its real dimension, since, in the classroom, they get inspiration from their own elementary school teaching experiences to teach beginners and future teachers. This way, it was possible to observe that these professionals maintain teaching supported on the research they do, in the view of today s professionals necessities, to act socially. At the same time, it was evidenced, through the repercussion of their conceptions on elementary teaching in higher education, that the participant teachers center their pedagogical activities aiming at developing the language abilities, just as it is pointed out in recent studies by the language professionals.